Silage Management: important practices often overlooked - K.K. Bolsen; B.E. Brent; M.K. Siefers; M.E. Uriarte (Kansas Agricultural Experiment Station Research Reports, 2000)
Four important silage management practices that are in the control of livestock producers and that are sometimes poorly implemented or overlooked entirely include: inoculating, packing, sealing, and managing the feedout face.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Silage; Silage storage